2009
DOI: 10.1007/s11164-009-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

A pulse radiolysis study of free radicals formed by one-electron oxidation of the antimalarial drug pyronaridine

Abstract: Free radicals from one-electron oxidation of the antimalarial drug pyronaridine have been studied by pulse radiolysis. The results show that pyronaridine is readily oxidised to an intermediate semiiminoquine radical by inorganic and organic free radicals, including those derived from tryptophan and acetaminophen. The pyronaridine radical is rapidly reduced by both ascorbate and caffeic acid. The results indicate that the one-electron reduction potential of the pyronaridine radical at neutral pH lies between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In OH reaction the 450 nm absorbance was also attributed to the aminophenoxy radical forming in dehydration of the hydroxycyclohexadienyl intermediate. The dehydration is fast process taking place on the few ms timescale [10,14,19]. Bisby [2] suggested a similar mechanism for the OH þ AQ reaction:…”
Section: Introductionmentioning
confidence: 98%
“…In OH reaction the 450 nm absorbance was also attributed to the aminophenoxy radical forming in dehydration of the hydroxycyclohexadienyl intermediate. The dehydration is fast process taking place on the few ms timescale [10,14,19]. Bisby [2] suggested a similar mechanism for the OH þ AQ reaction:…”
Section: Introductionmentioning
confidence: 98%
“…1 Our strategy has been to identify compounds that initiate antiparasitic drug action from distonic anion radical cascades, 17 using an automated, non-biological screen that could be converted into a high-throughput mode using robotic auto-samplers. 18 We have previously reported that pulsed radiolysis 19 and subsequent negative ion electrospray mass spectrometry 20 were ideally suited to this task and have now identified selected cinnolines as potential antiparasitic agents. 21 In general, densely substituted cinnolines are difficult to construct in a reproducible manner, and to the best of our knowledge, one-pot methods from commercially available raw materials are rare.…”
mentioning
confidence: 99%